TINJAUAN KELENGKAPAN PADA RESUME MEDIS PASIEN JKN RAWAT INAP DALAM MENUNJANG EFEKTIVITAS KLAIM JKN DI RUMAH SAKIT ISLAM SITI KHADIJAH PALEMBANG TRIWULAN 1 - Yessy Wirani; Nur Inda Fadhlika Qoyum; Tita Masda Febriyana (LPPM STIKes Mitra Adiguna, 2024)
The completeness of filling in the medical patient resume for inpatient care under the national health insurance (JKN) at RSI Siti Khadijah Palembang is still inadequate, such as patient identification, important notes, and writer authentication. This has an impact on the medical recordkeeping job, as the processed data from the medical resume is used as the basis for hospital report generation, decision-making by leadership, especially service quality evaluation, and supports the orderly administration of claim submissions. The research objective is to analyze the completeness of filling in the medical patient resume form for inpatient care under the national health insurance (JKN) to support the effectiveness of JKN claims at Rumah Sakit Islam Siti Khadijah Palembang in the first quarter of 2023. The type of research is quantitative research with a descriptive approach. The percentage results show that patient identification is 100% complete, important notes are 82% complete, writer authentication is 95% complete, and comprehensive notes are declared complete at 59%. A total of 84% of medical records are considered complete, while 16% are incomplete. The average of the four components analyzed is declared to not meet the national quality indicator standards based on the Minister of Health Regulation/Number /129/Menkes/SK/II/2008 regarding the minimum service standards for 100% completeness of medical records. Even though coding has utilized the Click Medik application, which enhances the effectiveness of the casemix coding system, the incompleteness of other components affects the claiming process. Writer authentication significantly influences the validity of the medical resume content, while the comprehensive notes component impacts the effectiveness of medical record performance and administration.